2016
DOI: 10.1111/1468-2427.12403
|View full text |Cite
|
Sign up to set email alerts
|

Durable Domestic Dreams: Exploring Homes in Estonian Socialist‐era Summerhouse Settlements

Abstract: ‘Home’ and the connotations of this term are little understood in the context of post‐socialist Central and Eastern Europe. While modern suburban living was rather unusual in this region under socialism, more and more people live in suburbia today. This article concerns itself with the homes of residents in the former socialist‐era summerhouse settlements in Estonia. Its aim is to further an understanding of the origins and (dis)continuities of the notion of home for individuals living in a post‐socialist envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…It was also part of a wider spectrum of informal housing practices that stretched across the 'actually existing socialisms' of Central and Eastern Europe where housing was in "perpetual short supply" (Nuga et al 2016: 868;see Szelényi, 1983;Zegarac, 1999). As a number of studies have shown, this encompassed a range of informal arrangements from the occupation and communal use of dilapidated tenements in inner-city districts to the construction of socialist summerhouse settlements (including dachi) on the peri-urban fringe (see Lovell, 2003;Nuga et al, 2016). While Schwarzwohnen may have, in other words, represented a local response to substandard living conditions, it was, symptomatic of a much wider ecosystem of housing insecurity that helped to shape the nature of urbanity in socialist cities despite the efforts of the state to supress marginality and informality (see Hirt, 2013: s34).…”
Section: 'Makeshift' Socialismsmentioning
confidence: 99%
“…It was also part of a wider spectrum of informal housing practices that stretched across the 'actually existing socialisms' of Central and Eastern Europe where housing was in "perpetual short supply" (Nuga et al 2016: 868;see Szelényi, 1983;Zegarac, 1999). As a number of studies have shown, this encompassed a range of informal arrangements from the occupation and communal use of dilapidated tenements in inner-city districts to the construction of socialist summerhouse settlements (including dachi) on the peri-urban fringe (see Lovell, 2003;Nuga et al, 2016). While Schwarzwohnen may have, in other words, represented a local response to substandard living conditions, it was, symptomatic of a much wider ecosystem of housing insecurity that helped to shape the nature of urbanity in socialist cities despite the efforts of the state to supress marginality and informality (see Hirt, 2013: s34).…”
Section: 'Makeshift' Socialismsmentioning
confidence: 99%
“…However, this is just part of the story as the rapidly increased car use has resulted in traffic jams and parking problems to the scale unseen under the socialist automobility regime (Argenbright, ; Lonkila, ). Similarly, the increasing withdrawal from cities to suburbs and gated communities happening in the metropolitan regions of the former Soviet Union and Central and Eastern Europe (Nuga, Leetmaa, & Tammaru, ), means also restrictions to ones' own freedom (see Hirt, on privatism). Suburbanisers are not just free to drive but forced so as the places they live in lack alternatives.…”
Section: Mobility and Freedommentioning
confidence: 99%